Prawne i medyczne aspekty modyfikacji aktywności wszczepialnych urządzeń do elektroterapii serca u pacjentów u kresu życia - Zoń, Anna Maria; Zoń, Katarzyna Maria (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
At the beginning of our considerations, it should be pointed out that cardiovascular diseases are the reason for almost half of deaths in Poland. Some disorders of the cardiovascular system are treated with cardiac implantable electronic devices.The aim of this paper is a comprehensive analysis of the issue regarding management of cardiac implantable electronic devices (peacemaker and cardioverter-defibrillator). In this respect it is significant to explain the legal status of these devices and the basic medical issues in the above scope (the type of devices, their similarities and differences). It is necessary for further consideration. In the scientific paper the management of cardiac implantable electronic devices both in legal and medical aspects is studied. In this context such problems as the patient’s consent and the obligation to be provided with medical information are analysed. In addition it should indicate how, why, when and in which scope the devices could be managed. What is more, the subject matter is taken into consideration concerning medical futility.Finally, the conclusions of the analysis are presented.
Keywords: patient’s consent; the obligation to be provided with medical information; patient’s autonomy; cardiac implantable electronic devices; medical futility